2000
DOI: 10.1007/s004170000174
|View full text |Cite
|
Sign up to set email alerts
|

Combined clear cornea phacoemulsification and trabecular aspiration in the treatment of pseudoexfoliative glaucoma associated with cataract

Abstract: It seems that the combined clear cornea phaco and trabecular aspiration procedure in cases of PEX glaucoma associated with cataract is a safe and effective method. This technique controls IOP more effectively and with fewer postoperative medications than clear cornea phaco alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 14 publications
2
34
0
2
Order By: Relevance
“…Frequent but minor complications of trabecular aspiration were localized descemetolysis (21.4-23 %) and blood reflux (14.2-52 %) [14,17], but there were no complications associated with postoperative ocular hypotony.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Frequent but minor complications of trabecular aspiration were localized descemetolysis (21.4-23 %) and blood reflux (14.2-52 %) [14,17], but there were no complications associated with postoperative ocular hypotony.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the risk profile of phacoemulsification/ trabecular aspiration [14,17] is obviously more favourable than that of combined phacoemulsification and trabeculectomy [14]. Frequent but minor complications of trabecular aspiration were localized descemetolysis (21.4-23 %) and blood reflux (14.2-52 %) [14,17], but there were no complications associated with postoperative ocular hypotony.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by the American Academy of Ophthalmology that evaluated papers with higher levels of evidence, the average amount of IOP drop after phacoemulsification in PXS was shown to be approximately 20%. Georgopoulos et al 27 prospectively studied controlled pseudoexfoliative glaucoma cases and demonstrated that cataract surgery resulted in an IOP drop from 18.7 to 16.7 mm Hg, a reduction of 2.0 mm Hg (11%). In another study by Damji et al 6 on Greek, Canadian and American patients with mild pseudoexfoliative glaucoma, phacoemulsification resulted in long-term postoperative IOP reduction of 16% from 19.8 to 16.7 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Je nach Operateur werden zwischen 3 bis 6 Uhrzeiten ohne gonioskopische Sicht behandelt. Randomisierte Studien erbrachten eine signifikant stärkere Drucksenkung durch die kombinierte Phakoemulsifikation (Phako) plus TA im Vergleich zur alleinigen Phako beim PEXG [6,7]. Historische Vergleichsgruppen zeigten aber auch, dass die kombinierte Phako plus TA nicht so stark drucksenkend wirkt wie die Kombination aus Phako und Trabekulektomie und wohl auch nicht so stark wirkend ist wie die Kombination aus Phako plus Trabektom [7,8].…”
Section: Trabekelaspiration Hintergrundunclassified